Marketing Mix and Trust Analysis on Medical Check Up Interest in Eka Hospital Pekanbaru - Rosarima Purba; Zulkanain Zulkanain; Alvi Furwanti Alwie (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2018)
One of many ways to prevent diseases to recognize the health condition is through medical check up. It detects early abnormalities in human body functions which potentially cause diseases. Medical check up may also serve as a routine health check for people with chronic diseases. Eka Hospital is one of the private hospitals which provides medical check up services. It is found instability in the number of the medical check up patients from year to year. This research was conducted to analyze marketing mix variables covering product, price, promotion, and place (4P) aspect and trust in the medical check up interest. The used research instrument is a questionnaire distributed to 145 respondents who had never used medical check up service at Eka Hospital. The results of the questionnaire were analyzed using descriptive analysis method and Structural Equation Modeling (SEM) using SmartPLS 3 tools. The result of the analysis showed that the “product” marketing mix did not significantly affect the trust and interest. The “pricing” marketing mix has a significant effect on the interest, however it has no significant effect on the trust. The “promotion” marketing mix has a significant effect on the interest, with no significant effect on the trust. The “place” marketing mix has no significant effect on both interest and trust. It is suggested that medical check up products need to be informed further to the public. Through having more consideration to promotion / communication aspects, it means that more attention is given to product information, price, quality and consumer requirements. This research would be enhanced if a broader community is involved.